Trace Element and Isotope Systematics in Vent Fluids and Sulphides From Maka Volcano, North Eastern Lau Spreading Centre: Insights Into Three-Component Fluid Mixing - Klose, Lukas; Keith, Manuel; Hafermaas, Daniel; Kleint, Charlotte; Bach, Wolfgang; Diehl, Alexander; Wilckens, Frederike; Peters, Christian; Strauss, Harald; Klemd, Reiner; van Geldern, Robert; Haase, Karsten Matthias; et al. (Frontiers in Earth Science, 2021)
Back-arc spreading centres and related volcanic structures are known for their intense hydrothermal activity. The axial volcanic edifice of Maka at the North Eastern Lau Spreading Centre is such an example, where fluids of distinct composition are emitted at the Maka hydrothermal field (HF) and at Maka South in 1525 to 1543 m water depth. At Maka HF black smoker-type fluids are actively discharged at temperatures of 329°C and are characterized by low pH values (2.79 - 3.03) and a depletion in Mg (5.5 mmol/kg) and SO4 (0.5 mmol/l) relative to seawater. High metal (e.g., Fe up to ~6 mmol/kg) and rare earth element (REE) contents in the fluids, are indicative for a rock-buffered hydrothermal system at low water/rock ratios (2-3). At Maka South, venting of white smoke with temperatures up to 301°C occurs at chimneys and flanges. Measured pH values range from 4.53 to 5.42 and Mg (31.0 mmol/kg), SO4 (8.2 mmol/l), Cl (309 mmol/kg), Br (0.50 mmol/kg) and Na (230 mmol/kg) are depleted compared to seawater, whereas metals like Li and Mn are typically enriched together with H2S. We propose a three-component mixing model with respect to the fluid composition at Maka South including seawater, a boiling-induced low-Cl vapour and a black smoker-type fluid similar to that of Maka HF, which is also preserved by the trace element signature of hydrothermal pyrite. At Maka South, high As/Co (>10 to 100) and Sb/Pb (>0.1) in pyrite are suggested to be related to a boiling-induced element fractionation between vapour (As, Sb) and liquid (Co, Pb). By contrast, lower As/Co (<100) and a tendency to higher Co/Ni values in pyrite from Maka HF likely reflect the black smoker-type fluid. The Se/Ge ratio in pyrite provides evidence for fluid-seawater mixing, where lower values (<10) are the result of a seawater contribution at the seafloor or during fluid upflow. Sulphur and Pb isotopes in hydrothermal sulphides indicate a common metal(loid) source at the two vent sites by host rock leaching in the reaction zone, as also reflected by the REE patterns in the vent fluids.